The impact of five key tourism supply chain sectors on tourists’ satisfaction of cultural heritage tourism in Melaka, Malaysia - Jaharuddin, Nor Siah; Dato’ Mansor, Zuraina; Mohamed, Azali (Universal Publishers, 2023)
Purpose: Many past studies have focused tourists satisfaction as one general area, without differentiating it to five supply chain sectors which are involved in the provision and consumption of tourism products. Thus, this study aims to investigate those five most critical supply chain sectors (namely transportation, accommodation, foods & craft, excursion & activities, and destination) that contribute to tourists' satisfaction and as sources of superior performance in enhancing and sustaining the image of a cultural heritage tourism destination. Design/methodology/approach: From 250 questionnaires distributed to the selected international tourists in Melaka using convenience sampling, about 211 questionnaires are deemed valid and useful for PLS data analysis. Findings: The findings show that the experience of food amenities and cultural heritage destination sectors has effects on tourists’ satisfaction. Meanwhile, the other sectors such as transportation, accommodation, and excursion & cultural activities were insignificant. Research limitations/implications: The study shed light on the strength of each tiers or supply chain sectors in contributing towards the competitive advantage of the tourism industry in Malaysia. Hence, this study provides useful information to tourism practitioners and academicians on the importance of experience as a key driver for tourists’ satisfaction and repeat visits. Practical implications: The study could provide insights for directing resources, ultimately improving and sustaining Melaka’s tourism image, competitiveness, and performance as the destination choice among the tourists. Hence, practitioners may gain a clearer understanding of the industry on how they fit in and predict future opportunities. Originality/value: In addressing the importance of tourists’ experience and satisfaction in the specific destination, each supply chain sector needs to be identified, their strengths and constraints tackled, and the value-adding along each industry chain has to be determined.